∵tan(α-5π)=tan(α-5π+6π)
=tan(α+π)=tanα
∴tanα=-4/3
∵π<α<2π
∴3π/2<α<2π
{sinα/cosα=-4/3
{sin²α+cos²α=1
{cosα>0,sinα<0
解得sinα=-4/5,cosα=3/5
∴sin(3π-α)=sin(π-α)=sinα=-4/5
cos(α-7π)=cos(α+π)=-cosα=-3/5
tan(α-5π)=-4/3
∴tan(α)=-4/3
∵π<α<2π
∴3π/2<α<2π
∴sinα=-4/5,cosα=3/5
∴sin(3π-α)和cos(α-7π)
=sin(π-α)和cos(α-π)
=sinα和-cosα
∴sin(3π-α)=-4/5
cos(α-7π)=3/5
tan(α-5π)=-4/3
tan(5π-α)=4/3]
tan(π-α)=4/3
tanα=-4/3 (取第二象限)
1+tan²α=1/cos²α=25/9
cosα=-3/5
sinα=√1-cos²α=4/5
sin(3π-α)=sinα=4/5
cos(α-7π)=cos(7π-α)=cos(π-α)=-cosα=3/5